Ultraviolet plasmonic enhancement of the native fluorescence of tryptophan on aluminum nano-hole arrays. (22nd January 2021) - Lee, Ji-Young; Cheng, Xueling; Wang, Yunshan
Abstract: The native fluorescence of biomolecules has been used in analytical chemistry to determine the concentration of an analyte. However, detecting biomolecules based on their intrinsic fluorescence at low concentration is challenging due to their small quantum yield and poor photon stability. Ultraviolet plasmonics have been reported to increase the photon yield and the photon stability of the native fluorescence of biomolecules such as DNA, peptides, and proteins. However, the experimentally reported count rate, or net enhancement factor, is small-with < 80× for DNA and < 14× for amino acids. Here we report native fluorescence enhancement of tryptophan on aluminum hole-arrays. By optimizing excitation geometry and the hole spacings, we are able to achieve a 47× net enhancement factor, the highest reported in the literature for tryptophan molecules. We conducted photobleaching experiments and observed a 2.3× reduction in the fast photon bleaching rate and 1.9× reduction in the slow photon bleaching rate on an aluminum hole-array with 300 nm periodicity compared to an aluminum thin film. The enhancement of the total photon yield reaches 58×, which is a result of the enhanced radiative rate. This study shows that periodic aluminum hole-arrays allow detection of tryptophan at concentration levels lower than previously reported, underpinning further research into label-free biosensing.